Model Pendampingan UMKM Pendukung Pariwisata Berbasis Desa Wisata: Studi Kasus Desa Wisata Sungai Langka, Kabupaten Pesawaran, Provinsi Lampung - Ni Made Ayu Windu Kartika; Meyliana Astriyantika; Enggar Dwi Cahyo; Deris Astriawan (Yayasan Literasi Sains Indonesia, 2026)
Community-based tourism development requires the systematic and sustainable integration of micro, small, and medium enterprises (MSMEs) into the tourism ecosystem. This study aims to formulate an ecosystem-based mentoring model for tourism-supporting MSMEs through a case study in Desa Wisata Sungai Langka. The research employed an applied case study approach. Data were collected through participatory observation, in-depth interviews, focus group discussions (FGDs), and documentation, then analyzed using the Miles and Huberman interactive model and gap analysis. The findings reveal significant gaps in attraction integration, amenity standards, digital promotion, and institutional coordination. The proposed model consists of four main components such as: capacity building, experience-based product strengthening, digitalization and branding, and collaborative institutional reinforcement. The results confirm that an ecosystem-based mentoring approach is more effective than a sectoral approach in integrating MSMEs into the village tourism value chain. This model offers a replicable framework for emerging tourism villages aiming to enhance competitiveness and sustainable local economic development.